2019
DOI: 10.3399/bjgp19x705461
|View full text |Cite
|
Sign up to set email alerts
|

Impact of integrating pharmacists into primary care teams on health systems indicators: a systematic review

Abstract: BackgroundEvidence suggests that pharmacists integrated into primary care can improve patient outcomes and satisfaction, but their impact on healthcare systems is unclear.AimTo identify the key impacts of pharmacists’ integration into primary care on health system indicators, such as healthcare utilisation and costs.Design and settingA systematic review of literature.MethodEmbase, MEDLINE, Scopus, the Health Management Information Consortium, CINAHL, and the Cochrane Central Register of Controlled Trials datab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 54 publications
(218 reference statements)
2
60
0
Order By: Relevance
“…Similarly, in a survey of fifty-six physicians in the state of North Carolina, 87.5% felt that identifying enhanced clinical outcomes was the top benefit of embedding a clinical pharmacist into their practice [ 50 ]. In addition to optimizing outcomes for patients, a systematic review found that pharmacists in PCTs reduced physician workload substantially [ 51 ]. Primary care physicians further described that the inclusion of a clinical pharmacist can improve the perceived quality of their patients’ healthcare, the quality of the medication decisions made, and the management of medications [ 29 ].…”
Section: Collaboration With Physiciansmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, in a survey of fifty-six physicians in the state of North Carolina, 87.5% felt that identifying enhanced clinical outcomes was the top benefit of embedding a clinical pharmacist into their practice [ 50 ]. In addition to optimizing outcomes for patients, a systematic review found that pharmacists in PCTs reduced physician workload substantially [ 51 ]. Primary care physicians further described that the inclusion of a clinical pharmacist can improve the perceived quality of their patients’ healthcare, the quality of the medication decisions made, and the management of medications [ 29 ].…”
Section: Collaboration With Physiciansmentioning
confidence: 99%
“…A systematic review found that emergency room visits decreased and savings in medication and health system costs were realized when pharmacists are integrated into PCTs, even with increased primary care usage [ 51 ]. Improvements in health outcomes at the individual and population level was also demonstrated when pharmacists work as a member of an inter-professional team, as well as decreased fragmentation within the healthcare system [ 51 ].…”
Section: Improved Outcomes For Patients and Optimization Of Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…Hitherto, physicians participating in several of these approaches adopted a substantial degree of pharmacists’ recommendations for medication change or deprescribing [ 13 , 17 , 18 ]. Though impact on clinical outcomes is difficult to detect from existing studies [ 19 ], collaborative care approaches revealed positive effects for patient-related, procedural and health-economic outcomes [ 13 , 20 23 ]. In a well-observed prospective cohort study in the UK, delegation to clinical pharmacists reduced GP-time spent on key prescribing activities by 51%, equating to 4.9 h of work per week being released [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…13,14 A recent systematic review of pharmacist integration into primary care practice showed that pharmacists can reduce primary care practitioners’ (PCPs’) workload and patients’ ER visits enabling the PCPs to see more patients and grow practices while reducing costs under accountable care organization payment arrangements. 15 On the other hand, a systematic review of 60 studies evaluating incorporation of pharmacists in primary care offices found no effect on clinical health outcomes, with some effect on patient-related outcomes and quality-of-care performance indicators. 16 Because accountable care organizations are rewarded financially for improvement of processes-of-care indicators, pharmacists’ incorporation could be beneficial.…”
Section: Data Synthesismentioning
confidence: 99%